HUBUNGAN TINGKAT KEPARAHAN GEJALA DAN STATUS FUNGSIONAL PADA PASIEN CARPAL TUNNEL SYNDROME DIUKUR MENGGUNAKAN CARPAL TUNNEL SYNDROME ASSESSMENT - Alif Luqman Hakim; Robby Tjandra (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2016)
Background : Carpal Tunnel Syndrome is an entrapment neuropathy due to pressure on the median nerve with one of the early symptom is pain. Pain that is present in patients with Carpal Tunnel Syndrome can make impairment of hand function, resulting in functional limitations to patients with Carpal Tunnel Syndrome in performing everyday activities.Aim : To determine the correlation between severity of symptoms and functional status in patients with Carpal Tunnel Syndromme measured using the Carpal Tunnel Syndrome Assessment Questionnaire.Method : This research is in the department of Physical Medicine and Rehabilitation. This research is a descriptive analytic study with cross sectional approach. Subjects were CTS patients in Dr. Kariadi Polyclinic Medical Rehabilitation Hospital that are pleased CTS patients fill out a questionnaire and meet the inclusion and exclusion criteria from March to June 2015. The correlation test is using Pearson correlation test.Result : The total number of samples inclusion in this study is 11 people. At the Pearson test showed a correlation between the two variables. Results of correlation between the severity of symptoms and functional status showed a significant correlation (p = 0.038) level of correlation is strong enough, (r = 0.628) with the direction of the positive correlation, so the higher the value the higher the severity of symptoms of the value of the functional status or getting ugly functional status.Conclusion : The severity of symptoms in patients with Carpal Tunnel Syndrome has a fairly strong positive correlation with functional status in patients with Carpal Tunnel Syndrome.